2019
DOI: 10.1002/pbc.28137
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic focal nodular hyperplasia after pediatric hematopoietic stem cell transplantation: The impact of hormonal replacement therapy and iron overload

Abstract: Background The advent of techniques for the assessment of iron overload (liver T2*‐MRI) has led to the awareness that focal nodular hyperplasia (FNH) represents a possible incidental finding after hematopoietic stem cell transplantation (HSCT), though its pathogenesis is still unclear. Methods We performed a retrospective analysis of the liver T2*‐MRI scans performed between 2013 and 2018 in a single pediatric HSCT Unit and recorded the number of patients with FNH (group A). Patients incidentally diagnosed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Focal nodular hyperplasia (FNH) is the second most common benign liver tumor in pediatrics, with an estimated incidence of 0.02% in childhood, comprising 2-4% of all pediatric liver tumors [110][111][112]. FNH is more common in adulthood; however, in the pediatric cohort, the median age reported is 8.7 years and is most commonly diagnosed around the age of six to ten, with rare case reports in infants [111,[113][114][115].…”
Section: Focal Nodular Hyperplasiamentioning
confidence: 99%
See 2 more Smart Citations
“…Focal nodular hyperplasia (FNH) is the second most common benign liver tumor in pediatrics, with an estimated incidence of 0.02% in childhood, comprising 2-4% of all pediatric liver tumors [110][111][112]. FNH is more common in adulthood; however, in the pediatric cohort, the median age reported is 8.7 years and is most commonly diagnosed around the age of six to ten, with rare case reports in infants [111,[113][114][115].…”
Section: Focal Nodular Hyperplasiamentioning
confidence: 99%
“…It is well reported that survivors of childhood cancers-specifically, extrahepatic solid tumors such as Wilms' tumor and neuroblastoma, as well as hematopoietic stem cell transplant (HSCT) recipients-are at increased risk of development of FNH. It is estimated that the incidence within this specific population is between 5% and 12% [110]. The mean time to develop FNH after treatment has been estimated to be between four and 12 years post therapy, with a shorter interval time period for those individuals who underwent chemotherapy along with HSCT [91].…”
Section: Associated Syndromes and Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Liver focal nodular hyperplasia (FNH) is an incidental finding frequently reported in these patients, with an estimated incidence remarkably higher than the general population. As HT plays a potential contributory effect on the onset of this condition [77], the use of transdermal 17βE may be associated with a reduction of its incidence, though no specific trials have been carried out so far. In addition, also patients with chronic iatrogenic hepatic toxicity may benefit from the avoidance of "hepatic first-passage effect" and transdermal route could be preferred in these cases.…”
Section: Pubertal Inductionmentioning
confidence: 99%
“…Although advances in the supportive care and monitoring of long-term survivors have dramatically improved in the last decades, iron overload is still a challenging issue and may be associated with late sequelae such as liver fibrosis, hepatic focal nodular hyperplasia, heart failure, hypogonadism and diabetes ( 158 , 159 ).…”
Section: Organ-specific Late Effects Of Hsct For Childhood and Adolescent Allmentioning
confidence: 99%